2013
DOI: 10.1007/s00586-013-3070-4
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical effects of cervical arthroplasty with U-shaped disc implant on segmental range of motion and loading of surrounding soft tissue

Abstract: Purpose Various design concepts have been adopted in cervical disc prostheses, including sliding articulation and standalone configuration. This study aimed to evaluate the biomechanical effects of the standalone U-shaped configuration on the cervical spine. Methods Based on an intact finite element model of C3-C7, a standalone U-shaped implant (DCI) was installed at C5-C6 and compared with a sliding articulation design (Prodisc-C) and an anterior fusion system. The range of motion (ROM), adjacent intradiscal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 28 publications
4
40
0
Order By: Relevance
“…The images were then imported into medical image processing software (Mimics 10.1, Materialise to reconstruct the vertebrae geometry volume of C 3 –C 7 (five vertebrae and four intervertebral discs). The finite element model was then created as a reference. Briefly, ABAQUS 6.10 (Simulia, Indianapolis, IN, USA) was used to build and mesh the cervical spine components and implant.…”
Section: Methodsmentioning
confidence: 99%
“…The images were then imported into medical image processing software (Mimics 10.1, Materialise to reconstruct the vertebrae geometry volume of C 3 –C 7 (five vertebrae and four intervertebral discs). The finite element model was then created as a reference. Briefly, ABAQUS 6.10 (Simulia, Indianapolis, IN, USA) was used to build and mesh the cervical spine components and implant.…”
Section: Methodsmentioning
confidence: 99%
“…Mo et al compared the DCI implanted at the segment C5-C6 with the Prodsic-C, ACDF (plate), and the intact spine in a finite element model. 10 ROM in flexion/extension increased by only 7% after DCI implantation but decreased by 30% and 20% in axial rotation and lateral bending, respectively. ACDF decreased ROM by 90% in all motions.…”
Section: Discussionmentioning
confidence: 89%
“…By contrast, it has been suggested that CDA preserves motion within the total physiologic ROM 22 and, moreover, extends the ROM of the involved segment. 5,10 This may exacerbate the stress on the index facet joints, 5,6,10 particularly in patients with preexisting cervical DDD. 23 The long-term effects of facet joint degeneration after CDA remain to be established, which may have a great impact on the physiologic decrease in ROM with aging.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations